Inhibition of Plasminogen Activator Inhibitor-1 Activation Suppresses High Fat Diet-Induced Weight Gain via Alleviation of Hypothalamic Leptin Resistance - Hosaka, Shinichiro; Yamada, Tetsuya; Takahashi, Kei; Dan, Takashi; Kaneko, Keizo; Kodama, Shinjiro; Asai, Yoichiro; Munakata, Yuichiro; Endo, Akira; Sugawara, Hiroto; Kawana, Yohei; Yamamoto, Junpei; et al. (Frontiers in Pharmacology, 2020)
Leptin resistance is an important mechanism underlying the development and maintenance of obesity and is thus regarded as a promising target of obesity treatment. Plasminogen activator inhibitor 1 (PAI-1), a physiological inhibitor of tissue-type and urokinase-type plasminogen activators, is produced at high levels in adipose tissue, especially in states of obesity, and is considered to primarily be involved in thrombosis. PAI-1 may also have roles in inter-organ tissue communications regulating body weight, because PAI-1 knockout mice reportedly exhibit resistance to high fat diet (HFD)-induced obesity. However, the role of PAI-1 in body weight regulation and the underlying mechanisms have not been fully elucidated. We herein studied how PAI-1 affects systemic energy metabolism. We examined body weight and food intake of PAI-1 knockout mice fed normal chow or HFD. We also examined the effects of pharmacological inhibition of PAI-1 activity by a small molecular weight compound, TM5441, on body weight, leptin sensitivities and expressions of thermogenesis-related genes in brown adipose tissue (BAT) of HFD-fed wild type (WT) mice. Neither body weight gain nor food intake was reduced in PAI-1 KO mice under chow fed conditions. On the other hand, under HFD feeding conditions, food intake was decreased in PAI-1 KO as compared with WT mice (HFD-WT mice 3.98±0.08g/day vs HFD-KO mice 3.73±0.07g/day, P=0.021), leading to an eventual significant suppression of weight gain (HFD-WT mice 40.3±1.68g vs HFD-KO mice 34.6±1.84g, P=0.039). Additionally, TM5441 treatment of WT mice pre-fed the HFD resulted in a marked suppression of body weight gain in a PAI-1-dependent manner (HFD-WT-Control mice 37.6±1.07g vs HFD-WT-TM5441 mice 33.8±0.97g, P=0.017). TM5441 treatment alleviated HFD-induced systemic and hypothalamic leptin resistance, before suppression of weight gain was evident. Moreover, improved leptin sensitivity in response to TM5441 treatment was accompanied by increased expressions of thermogenesis-related genes such as uncoupling protein 1 in BAT (HFD-WT-Control mice 1.00±0.07 vs HFD-WT-TM5441 mice 1.32±0.05, P=0.002). These results suggest that PAI-1 plays a causative role in body weight gain under HFD-fed conditions by inducing hypothalamic leptin resistance. Furthermore, they indicate that pharmacological inhibition of PAI-1 activity is a potential strategy for alleviating diet-induced leptin resistance in obese subjects.